Modulated Gut Microbiota for Potential COVID-19 Prevention and Treatment - Zhao, Shuai; Feng, Pengya; Meng, Wenbo; Jin, Weilin; Li, Xun; Li, Xiangkai (Frontiers in Medicine, 2022)
COVID-19, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has gained global attention. SARS-CoV-2 identifies and invades human cells via angiotensin-converting enzyme 2 receptors, which is highly expressed both in lung tissues and intestinal epithelial cells. The existence of the gut-lung axis in disease could be profoundly important for both disease etiology and treatment. Furthermore, several studies reported that infected patients suffer from gastrointestinal symptoms. The gut microbiota has a noteworthy effect on the intestinal barrier and affects many aspects of human health, including immunity, metabolism, and the prevention of several diseases. This review highlights the function of the gut microbiota in the host’s immune response, providing a novel potential strategy through the use of probiotics, gut microbiota metabolites, and dietary products to enhance the gut microbiota as a target for COVID-19 prevention and treatment.